2005
DOI: 10.2337/diacare.28.6.1451
|View full text |Cite
|
Sign up to set email alerts
|

Bimodality of 2-h Plasma Glucose Distributions in Whites

Abstract: OBJECTIVE -Several studies have shown a bimodal curve in the distribution of glucose in populations with a high prevalence of type 2 diabetes, but bimodality has not been reported among whites of Northern European ancestry. It is not clear whether this difference reflects the lower prevalence of diabetes, obscuring a second mode, or implies a more fundamental difference between whites and nonwhites. We investigate this issue by studying glucose distributions in older white patients. RESEARCH DESIGN AND METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
(22 reference statements)
2
26
0
Order By: Relevance
“…However, the estimated cut points were inconsistent between countries, especially for 2-h plasma glucose when participants with known diabetes were included. Comparing these results with those of earlier studies, we found that the overall cut point for FPG was somewhat lower (2,3,8,9), whereas the cut point for 2-h plasma glucose was well in line (1)(2)(3)5,8,10,11,13), except for the studies of South African Indians (9) and Western Samoans (12), which produced lower cut points for 2-h plasma glucose.…”
Section: -Distribution Of Fpg In Korea (A) and Nauru (B) And 2-h Plassupporting
confidence: 55%
See 2 more Smart Citations
“…However, the estimated cut points were inconsistent between countries, especially for 2-h plasma glucose when participants with known diabetes were included. Comparing these results with those of earlier studies, we found that the overall cut point for FPG was somewhat lower (2,3,8,9), whereas the cut point for 2-h plasma glucose was well in line (1)(2)(3)5,8,10,11,13), except for the studies of South African Indians (9) and Western Samoans (12), which produced lower cut points for 2-h plasma glucose.…”
Section: -Distribution Of Fpg In Korea (A) and Nauru (B) And 2-h Plassupporting
confidence: 55%
“…This exclusion potentially makes the two components less distinct and thereby decreases the probability of a meaningful cut point separating them. However, as acknowledged in previous studies (3,10,13), including patients with known diabetes in the analyses will induce a treatment bias for the following reasons. In accordance with existing treatment guidelines, patients with diabetes are treated with the aim of lowering their glucose to a near-normal range.…”
Section: -Distribution Of Fpg In Korea (A) and Nauru (B) And 2-h Plasmentioning
confidence: 99%
See 1 more Smart Citation
“…It contributes the majority of increased cases of morbidity and mortality, poor quality of life along with the economic burden on the existing healthcare systems independently for management and preventive approaches. The highly susceptible populations which show differences in the diagnostic criteria for DM are Mexican American [38], Pacific Islanders [39], South African Indians [40], Egyptians [41], Malaysians [42], and Americans in the United States [43]. Asian Indian phenotypes (abnormal clinical and biochemical disturbances seen in Indians) include IR, greater abdominal adiposity (waist circumference, WC), low body mass index (BMI) and occurrence of T2DM onset at an earlier age compared with Caucasians [44,45].…”
Section: What Is the Burden Of Dm?mentioning
confidence: 99%
“…If glucose concentrations are log-transformed to minimize the rightward skewness, a bimodal distribution has been noted (48). However, cutoff values defining the two distributions have ranged from 200–307 mg/dL, mostly depending on the ages of the population surveyed (38). …”
mentioning
confidence: 99%